Effects of Single Manual Medicine Treatment for Infants with Postural and Movement Asymmetries and Positional Preference: A Multicentre Randomised Controlled Trial – SMMT for IPMA - Sacher, Robby; Wuttke, Marc; Göhmann, Ulrich; Kayser, Christian; Knabe-Ulner, Kirsti; Ammermann, Elke; Ammermann, Michael; Krocker, Bodo; Fünfgeld, Liv; Spittank, Holger; Derlien, Steffen; Loudovici-Krug, Dana (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2022)
Objective The aim of the study was the evaluation of the effects of a single manual medicine treatment (SMMT) for infants with postural and motor asymmetries in upper cervical asymmetry disorder respectively kinematic imbalance due to suboccipital strain (KISS).Methods Design: Multicentre double-blind randomised study Subjects/Setting: 202 infants at the age of 14–24 weeks with postural and movement findings were examined in four study centres using the standardized 4-item Symmetry-Score (points: 4=symmetric to 17=asymmetric). The inclusion criterion was a score of at least 10 points. The intervention group (IG) received a SMMT, whereas the control group (CG) did not receive any manual therapy. In addition, the infants of both groups were trained with a home exercise programme by their parents.Statistical Methods The primary target parameter was the result of the Symmetry-Score, measured before the intervention and 4–6 weeks afterwards.Results 171 children were randomised (IG=83/CG=88). All infants enrolled were measured to the second time-point (Intention-to-treat-analysis). The average improvement of IG compared to CG in Symmetry-Score was 2.3 points (p<.001). Following the score definition 80% of IG and 49% of CG fell below the treatment threshold of 10 points. No side effects were observed.Conclusions The SMMT significantly improves postural and motor asymmetries in infants with KISS.
Keywords: infantile postural asymmetry; KISS; neonatal torticollis; infantile scoliosis